Multidisciplinary approaches for identification of Colchicum L. species in the flora of Turkey - Uncuoglu, Ahu Altinkut; Aydin, Yildiz; Senturk-Akfirat, Funda; Tuna, Metin; Nizam, Ilker; Kaya, Erdal (Elsevier Science Bv, 2012)
[No abstract available]
Eurobiotech Agriculture Symposium -- APR 12-14, 2012 -- Erciyes Univ, Kayseri, TURKEY